Quantitative assessment of histological changes in chronic gastritis after eradication of Helicobacter pylori. Issue 9 (September 1992) - Di Napoli, A; Petrino, R; Boero, M; Bellis, D; Chiandussi, L
Abstract : AIMS: To evaluate the effect of 10 day triple treatment on H pylori eradication and associated gastritis. METHODS: Fifty patients with H pylori positive non-ulcer dyspepsia were treated for 10 days with amoxicillin, tinidazole, and bismuth salts. Histological examination of the antral mucosa was performed before (T0), six weeks (T1), and six months (T2) after treatment. The new Sydney classification of gastritis was used, using a score from 0 to 3 to grade degree of inflammation, atrophy, activity (intraepithelial or lamina propria damage) and H pylori. RESULTS: At T0 all patients had chronic active gastritis. Lymphoid follicules were present in 12 cases. At T1 33 patients were H pylori negative: the score showed a decrease of activity (from 2.5 to 0.54). The result was confirmed at T2 (mean score 0.22). Inflammation decreased from 1.8 to 1.4 at T2. Only one case of follicular gastritis was observed. In H pylori positive patients the scores did not show significant modifications. CONCLUSIONS: Ten day triple treatment is effective in eradicating H pylori in 69% of cases, causing a decrease of the total score for gastritis. Activity, defined by polymorph infiltration, was promptly reduced when H pylori was eradicated. There was a trend to a reduction in inflammation, but atrophy was irreversible.